2023
DOI: 10.3390/ijms241311196
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Central Nervous System Barrier Impairment in Amyotrophic Lateral Sclerosis: Gender-Related Difference in Patients

Abstract: Central nervous system (CNS) barrier impairment has been reported in amyotrophic lateral sclerosis (ALS), highlighting its potential significance in the disease. In this context, we aim to shed light on its involvement in the disease, by determining albumin quotient (QAlb) at the time of diagnosis of ALS in a large cohort of patients. Patients from the university hospital of Tours (n = 307) were included in this monocentric, retrospective study. In total, 92 patients (30%) had elevated QAlb levels. This percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Q ALB is recognized as an effective marker to evaluate the permeability of the BBB ( Reiber and Peter, 2001 ). The current finding of the significant increase in Q ALB of ALS patients was consistent with some studies ( Wu et al, 2020 ; Alarcan et al, 2023 ). Some researchers believed that the disruption of BBB was an early event in ALS, and most studies suggested that BBB disruption in neurodegenerative diseases mediates the invasion of immune cells from the blood, resulting in neurodegeneration ( Aragón-González et al, 2022 ; Beaman et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Q ALB is recognized as an effective marker to evaluate the permeability of the BBB ( Reiber and Peter, 2001 ). The current finding of the significant increase in Q ALB of ALS patients was consistent with some studies ( Wu et al, 2020 ; Alarcan et al, 2023 ). Some researchers believed that the disruption of BBB was an early event in ALS, and most studies suggested that BBB disruption in neurodegenerative diseases mediates the invasion of immune cells from the blood, resulting in neurodegeneration ( Aragón-González et al, 2022 ; Beaman et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%